Toward Holistic Curriculum Management in Islamic Early Childhood Education: A Framework for Integrated Learning Development - Oki Dermawan; Defriyanto; Busmayaril; Trisna Kusuma Yusuf (Al-Qalam Institute, 2026)
This study aims to examine the implementation of holistic Islamic curriculum management in early childhood education and its contribution to comprehensive child development. The research employs a Systematic Literature Review (SLR) method by analyzing selected national and international publications from major academic databases. Articles were screened using predefined inclusion and exclusion criteria to ensure relevance and methodological rigor. The findings reveal that holistic Islamic curriculum management effectively integrates core values—aqidah (faith), ibadah (worship), and akhlaq (morality)—into learning processes through thematic, interactive, and child-centered approaches. This integration supports balanced development across spiritual, cognitive, social, emotional, and moral domains. The review also highlights the importance of participatory management involving teachers, parents, and community stakeholders, as well as continuous evaluation aligned with holistic educational objectives. However, challenges remain, including limited teacher capacity, inadequate resources, and inconsistencies in assessing character and religious outcomes. The study implies that strengthening holistic Islamic curriculum management requires sustained professional development, improved resource support, and enhanced stakeholder collaboration. These efforts are essential to optimize character education and promote integrated child development in Islamic early childhood education contexts.